Critical Synthesis Package: Professionalism Mini-Evaluation Exercise (P-MEX) - Molly Gathright (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Professionalism Mini-Evaluation Exercise (P-MEX), and (2) a copy of the P-MEX instrument developed by Richard L. Cruess, MD. The P-MEX is an evaluation instrument used to assess professionalism in clinical training through a faculty-observed encounter of trainee's behavior either with or without patients. Utilizing a 4-point Likert-type scale, the trainee is evaluated on 24 different directly observable items of medical professionalism which assess skills related to: the doctor-patient relationship, reflection, time management, and interprofessional relationships. A validation study demonstrated construct validity through factor analysis, and a generalizability analysis and decision study revealed acceptable internal consistency with a reproducibility coefficient of 0.8. Further validation studies have been performed in cross-cultural contexts. Originally developed for medical student population, the P-MEX has been extended for use in residents and fellows. It demonstrates thoughtful development, good feasibility of use, and validity for its intended populations. Additionally, it does not require excessive evaluator training and may be used as a formative assessment. There is low reliability when using this tool for peer-to-peer evaluation and the phenomenon of "failure to fail" may occur with faculty evaluators. Finally, evidence of educational effect is lacking in the literature, as no studies examine whether the instrument improves learning, clinical skills, or patient care.